BEYOND LECTURES: COMPARING FOCUS GROUP DISCUSSION AND ROLE-PLAY METHODS FOR INDONESIAN SUBURBAN STUNTING EDUCATION - Febrian, Alfito Faishal; Fahreizy, Abdillah Zidan; Azizah, Maghfira Rahma; Asmara, Prita Amira Windy; Jihan, Farhanaz; Dewi, Lula Kamila; Zahra, Shafira Aulia; Ratri, Devita Rahmani; Dhuha, Nur Syamsu (Journal of Community Health and Preventive Medicine, 2026)
Stunting remains a major global health problem affecting millions of children. Although Indonesia’s national stunting prevalence is declining, the rate in Singosari Sub-district increased to 3.5% in 2024, with Candirenggo Village consistently experiencing a high burden despite easy access to nearby markets. This highlights the need to improve caregivers’ knowledge of healthy nutrition and parenting practices. This quasi-experimental study compared the effectiveness of Focus Group Discussions (FGDs) and role-playing, following a standard lecture, in improving caregivers’ stunting knowledge. During the pre-intervention phase, 38 caregivers completed questionnaires exploring determinants of stunting; 20 proceeded to the intervention phase, received the lecture, and were equally assigned to FGD or role-playing groups. The Wilcoxon signed-rank test showed that both methods significantly improved 20 caregivers’ knowledge (mean improvement: 20.00 ± 17.17; p < 0.001), with no significant difference between the FGD and role-playing groups (16.00 ± 19.55 vs. 24.00 ± 14.30; p = 0.310). Both methods are effective educational strategies for improving short-term caregiver knowledge of stunting.